Different Signals Control Laminar Specificity of Commissural and Entorhinal Fibers to the Dentate Gyrus - Zhao, Shanting (J Neurosci, 2003)
The factors governing the characteristic laminated termination of hippocampal afferents are essentially unknown. Principally, diffusible factors of the target region, membrane-bound molecules on the ingrowing afferent fibers and on the postsynaptic target cells as well as molecules of the extracellular matrix (ECM), may play a role. Using slice cocultures as a model, we show that hyaluronic acid, an ECM molecule, is essential for the segregated, layer-specific termination of entorhinal fibers but not of commissural afferents to the mouse dentate gyrus. Laminar specificity of the latter, in contrast, is determined by the position of the postsynaptic granule cells. Thus, malpositioning of the granule cells in slice cultures from reeler mutant mice altered the projection of commissural fibers from cocultured wild-type hippocampus. In contrast, commissural fibers from reeler mouse hippocampus formed a normal, sharply delineated projection to the inner molecular layer of cocultured wild-type dentate gyrus, precluding a cell-autonomous effect of the reeler mutation on commissural neurons. Interestingly enough, entorhinal fibers formed their normal, sharply delineated projection in cocultured reeler dentate gyrus despite the malpositioning of the target granule cells. Because hyaluronan-associated molecules are likely to control the segregated termination of entorhinal fibers, we compared immunolabeling for neurocan and chondroitin sulfate in sections from reeler and wild-type mice and found it similar in both genotypes. Together these results show that different mechanisms underlie the formation of commissural and entorhinal fiber layers during the development of the dentate gyrus.